Sistem Informasi Dalam Hubungan Prinsipal – Agen Di RSU-BLUD Bahteramas, Kota Kendari Provinsi Sulawesi Tenggara - Zainul Abidin (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
This study aims to analyze the information systems that occur, especially in terms of reporting procedures, budgeting systems and the role of the supervisory board at the Bahteramas Hospital, Kendari City, Southeast Sulawesi Province. This research uses a qualitative approach. The results show that the reporting procedure uses a combination of computers and manuals, but manual systems are still dominant. The budgeting system still uses conventional systems and also uses performance-based budgets. The supervisory board has carried out its duties, but it is still not optimal. Even so, there is complete information where the principal knows what the agent is doing. Even though in reality, there are still agency problems (moral hazard and adverse selection) both potentially and factually. For example, negligence in the supply of drugs, but on the whole does not hinder the disclosure of information by the principal.